Determine the Frequency of Vitamin D Deficiency in Polycystic Ovarian Syndrome Patients - Shazia Ashraf, Hina Khalil, Afshan Batool, Saleem Adil, Neha Ahuja (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Vitamin D deficiency can lead to various comorbidities including fertility issues among females. Polycystic ovarian syndrome is a main fertility related issue of females requiring effective treatment protocols. Objective: To determine the frequency of vitamin D deficiency in polycystic ovarian syndrome patients. Study Design: Cross-sectional analytical study Place and Duration of Study: Department of Obstetrics & Gynaecology, Gujranwala Medical College, Gujranwala from 1st April 2023 to 30th September 2023. Methodology: A total of 100 cases diagnosed through clinical assessment, follicle stimulating hormones and luteinizing hormone ratios (abnormal as 3:1) and confirmed for polycystic ovarian morphology through ultrasound were included in this study. The tests included fasting glucose, homeostatic model assessment of insulin resistance (HOMA-IR), mean 25-hydroxyvitamin D3 [25(OH)D3], serum testosterone, follicle stimulating hormones and luteinizing hormone. The anthropometric measurements including body mass index and waist circumference were taken of each patient through digital weight and height measuring machine while inch in tape measuring waist circumference was also applied. The patients having 25(OH)D3 levels <30 ng/ml (10-29) were categorized as in Group I with vitamin D deficiency while those having >30 ng/ml vitamin D levels were categorized as in Group II with normal vitamin D levels. A comparative analysis of various variables was performed within both groups. Results: There were 60% of those who were having vitamin D deficiency, while 40% were having normal vitamin D levels presented. The patients were between 16-35 years of age. The body mass index of those females having vitamin D deficiency in Group I were having higher body mass index than normal vitamin D level patients in group II. The fasting glucose levels as well as HOMA-IR of Group I patients was higher than Groups II (92.6±12.4 vs 80.2±9.9 mg/dl and 3.8±1.1 vs 3.4±0.9) respectively. The mean levels of Vitamin D in group I was 12.7±3.3ng/mL in comparison to the mean value of vitamin D as 33.1±7.8ng/ml in Group II. An elevated serum testosterone in Group I was 7.4±2.2vs 5.3±0.9 ng/ml. The FSH:LH ratio was severely affected in Group I who were vitamin D deficient females in comparison to the normal vitamin D Group II patients. There is a negative correlation between the vitamin D levels and body mass index, HOMA-IR, serum hormonal levels including serum follicle stimulating hormones, luteinizing hormone and testosterone levels. Conclusion: Around 60% of polycystic ovarian syndrome females were having 25(OH) vitamin D3 deficiency in them. Keywords: Frequency, Vitamin D deficiency, Polycystic ovarian syndrome